Efektifitas Telenursing Dalam Pemantauan Tekanan Darah Pada Pasien Dengan Hipertensi: Literature Review - Roswita, Ria; Nurhayati, Nurhayati (Jurnal Skala Kesehatan, 2024)
Hypertension is a non-communicable disease (NCD) and the main chronic disease which is the cause of death in the world and the highest cause of stroke and coronary heart disease. One effective method, namely monitoring blood pressure, can now be done using technology, namely telenursing. This study is a literature review which aims to determine the effect of monitoring using telenursing on reducing blood pressure in hypertensive patients. This literature review analyzes 10 articles originating from journal databases, namely Google Scholar, Proquest and Science Direct with the keywords "telenusing", "blood pressure" and "hypertension". The results of the analysis show that telenursing can reduce blood pressure and improve blood pressure control in hypertensive patients. In general, telenursing can improve self-management in controlling hypertension at home. It is hoped that the results of this literature review will be used as material for improving the quality of telenursing.